Optical adhesive sheet

JP2025023631APending Publication Date: 2025-02-17NITTO DENKO CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023127949
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-08-04
Publication Date
2025-02-17

AI Technical Summary

Benefits of technology

【0019】 本発明の光学粘着シートは、上記のように、ベースポリマーと、光重合性多官能化合物と、光重合開始剤とを含む。そのため、光学粘着シートは、光硬化前の柔らかい状態で被着体の段差付き表面に貼り合わせることができる(貼り合わせ後に光硬化させることができる)。そして、光硬化前の光学粘着シートは、段差追従性試験において50μm以上の追従可能段差dを少なくとも一つ有し、且つ、光学粘着シートの厚さDに対する追従可能段差dの比率が0.4以上0.8以下である。このような光学粘着シートは、段差付き表面を有する被着体に対する貼り合わせにおいて、良好な段差追従性を実現するのに適する。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025023631000001_ABST
    Figure 2025023631000001_ABST
Patent Text Reader

Abstract

To provide an optical adhesive sheet suitable for balancing step-filling capability and joining reliability.SOLUTION: An adhesive sheet 10 includes a base polymer, a photopolymerizable polyfunctional compound, and a photopolymerization initiator. The adhesive sheet 10 has at least one followable step d of 50 μm or more in a predetermined step-following test, where the ratio of the followable step d to the thickness D of the adhesive sheet 10 is 0.4 or more and 0.8 or less. The adhesive sheet 10 has an adhesive strength B1 of 1.5 MPa or more in a predetermined first tensile test.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an optical pressure-sensitive adhesive sheet. [Background technology]

[0002] A display panel has a laminated structure including elements such as a pixel panel, a polarizing film, and a cover glass. In the manufacturing process of a display panel, for example, an optically transparent adhesive sheet (optical adhesive sheet) is used to bond the elements included in the laminated structure. An optical adhesive sheet for use in a display panel is described in, for example, Patent Document 1 below. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2010-97070 A Summary of the Invention [Problem to be solved by the invention]

[0004] The laminated structure of the display panel includes an element having a surface step. For example, a decorative or light-shielding printed layer is provided on the edge of the pixel panel side surface of the cover glass. The printed layer is provided, for example, around the entire edge of the cover glass. This printed layer has a predetermined thickness. Therefore, on the pixel panel side of the cover glass, there is a step (printed step) between the cover glass surface and the printed layer surface. Therefore, the optical adhesive sheet for display panel use is required to be soft enough to follow the printed step (step followability). Insufficient step followability of the optical adhesive sheet is undesirable, for example, because it causes air bubbles to be formed along the printed layer between the optical adhesive sheet attached to the printed layer surface of the cover glass and the cover glass.

[0005] From the viewpoint of conformability to unevenness, a softer optical pressure-sensitive adhesive sheet is preferable. However, in conventional optical pressure-sensitive adhesive sheets, the softer the sheet, the lower the bonding reliability after bonding between adherends by the optical pressure-sensitive adhesive sheet.

[0006] The present invention provides an optical adhesive sheet suitable for achieving both step conformability and bonding reliability. [Means for solving the problem]

[0007] The present invention [1] is an optical adhesive sheet comprising a base polymer, a photopolymerizable multifunctional compound, and a photopolymerization initiator, and having at least one conformable step d of 50 μm or more in the step conformability test described below, and a ratio of the conformable step d to a thickness D of the optical adhesive sheet of 0.4 or more and 0.8 or less, and an adhesive strength B1 of 1.5 MPa or more in the first tensile test described below.

[0008] Step-following test: First, a glass plate (length 100 mm x width 50 mm) having a first surface and a second surface opposite to the first surface, a polyethylene terephthalate film (length 100 mm x width 50 mm), and a sample sheet (length 75 mm x width 45 mm) of the optical adhesive sheet are prepared. A printed layer having a thickness h of 50 μm or more is formed on the first surface of the glass plate around the entire edge of the glass plate. The printed layer is formed in a range of 15 mm inward from each end of the glass plate in the length direction of the glass plate, and in a range of 5 mm inward from each end of the glass plate in the width direction of the glass plate.

[0009] Next, the first surface side of the glass plate and the polyethylene terephthalate film are bonded in the thickness direction via the sample sheet arranged at the center of the glass plate in the length direction and the width direction, to obtain a first bonded body. In the first bonded body, the printed layer is sandwiched between the glass plate and the sample sheet within a range of 2.5 mm outward from the inner end of the printed layer.

[0010] Next, the first bonded body is heat-treated under conditions of 50° C., 0.5 MPa and 15 minutes.

[0011] Next, the sample sheet in the first bonded body is irradiated with an integrated light quantity of 3000 mJ / cm 2 The resin is photocured by exposure to ultraviolet light.

[0012] Next, the inside of the inner edge of the printed layer from the polyethylene terephthalate film side of the first bonded body is observed with a digital microscope at an observation magnification of 20. Then, when no air bubbles are confirmed within the observed range, the thickness h is determined as the conformable step d.

[0013] First tensile test: First, the first alkali glass plate and the second alkali glass plate are bonded in the thickness direction via the optical adhesive sheet to obtain a second bonded body. Next, the optical adhesive sheet is irradiated with an integrated light amount of 3000 mJ / cm. 2 The second bonded body is then heat-treated at 50°C, 0.5 MPa, and 15 minutes. The first and second alkali glass plates in the second bonded body are then pulled in opposite directions in the thickness direction at 85°C and a pulling speed of 25 mm / min to measure the adhesive strength B1.

[0014] The present invention [2] includes the optical adhesive sheet described in the above [1], which has an adhesive strength B2 in the second tensile test described below, and the ratio of the adhesive strength B2 to the adhesive strength B1 is 2.0 or more and 3.5 or less.

[0015] Second tensile test: First, the first alkali glass plate and the second alkali glass plate are bonded in the thickness direction via the optical adhesive sheet to obtain a third bonded body. Next, the optical adhesive sheet is irradiated with an integrated light amount of 3000 mJ / cm. 2The third bonded body is then heat-treated at 50°C, 0.5 MPa, and 15 minutes. The first and second alkali glass plates in the third bonded body are then pulled in opposite directions in the thickness direction at 25°C and a pulling speed of 25 mm / min to measure the adhesive strength B2.

[0016] The present invention [3] includes an optical adhesive sheet described in [1] or [2] above, which has an adhesive strength B3 in the third tensile test described below, and the ratio of the adhesive strength B3 to the adhesive strength B1 is 3.0 or more and 4.2 or less.

[0017] Third tensile test: First, the first alkali glass plate and the second alkali glass plate are bonded in the thickness direction via the optical adhesive sheet to obtain a fourth bonded body. Next, the optical adhesive sheet is irradiated with an integrated light amount of 3000 mJ / cm. 2 The fourth bonded body is then photocured by irradiating it with ultraviolet light at 50°C, 0.5 MPa, and 15 minutes. The first and second alkali glass plates in the fourth bonded body are then pulled in opposite directions in the thickness direction at -20°C and a pulling speed of 25 mm / min, to measure the adhesive strength B3.

[0018] The present invention [4] includes an optical adhesive sheet according to any one of [1] to [3] above, in which the thickness D is 80 μm or more. Effect of the Invention

[0019] As described above, the optical adhesive sheet of the present invention contains a base polymer, a photopolymerizable polyfunctional compound, and a photopolymerization initiator. Therefore, the optical adhesive sheet can be attached to a stepped surface of an adherend in a soft state before photocuring (can be photocured after attachment). The optical adhesive sheet before photocuring has at least one followable step d of 50 μm or more in a step followability test, and the ratio of the followable step d to the thickness D of the optical adhesive sheet is 0.4 to 0.8. Such an optical adhesive sheet is suitable for achieving good step followability when attached to an adherend having a stepped surface.

[0020] In addition, as described above, the optical adhesive sheet of the present invention has an adhesive strength B1 (adhesive strength of the optical adhesive sheet after photocuring) of 1.5 MPa or more in the first tensile test. Such an optical adhesive sheet is suitable for achieving good bonding reliability after bonding between adherends.

[0021] Therefore, the optical pressure-sensitive adhesive sheet of the present invention is suitable for achieving both conformability to steps on the adherend surfaces when bonding the adherends together and bonding reliability after bonding the adherends together. [Brief description of the drawings]

[0022] [Figure 1] 1 is a schematic cross-sectional view of one embodiment of an optical adhesive sheet of the present invention. [Diagram 2] 1 shows the positional relationship between the glass plate and the pressure-sensitive adhesive sheet in the laminate used to evaluate the step-conforming ability of the examples and comparative examples. [Diagram 3] Schematic representation of the tensile tests (first tensile test, second tensile test, third tensile test). [Figure 4] This shows an example of a method for producing the optical adhesive sheet shown in Fig. 1. Fig. 4A shows a step of forming a coating film of the adhesive composition, Fig. 4B shows a step of forming a base adhesive sheet, Fig. 4C shows a step of peeling one of the release liners, Fig. 4D shows a step of supplying a post-added component to the base adhesive sheet, and Fig. 4E shows a step of bonding the release liner to the optical adhesive sheet. [Diagram 5] This shows an example of a method of using the optical adhesive sheet shown in Fig. 1. Fig. 5A shows a process of attaching the optical adhesive sheet to a member (adherend), Fig. 5B shows a process of joining members together via the optical adhesive sheet, and Fig. 5C shows a process of photocuring the optical adhesive sheet between the members. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0023] As shown in Fig. 1, an adhesive sheet 10 according to one embodiment of the present invention has a sheet shape of a predetermined thickness and extends in a direction (plane direction) perpendicular to a thickness direction H. The adhesive sheet 10 has an adhesive surface 11 and an adhesive surface 12 opposite to the adhesive surface 11. Fig. 1 exemplarily shows a state in which release liners 21, 22 are attached to the adhesive surfaces 11, 12 of the adhesive sheet 10. The release liner 21 is in releasable contact with the adhesive surface 11. The release liner 22 is in releasable contact with the adhesive surface 12.

[0024] The adhesive sheet 10 is an optically transparent adhesive sheet (optical adhesive sheet). The adhesive sheet 10 contains a base polymer, a photopolymerizable multifunctional compound (first photopolymerizable multifunctional compound), and a photopolymerization initiator, and has photocurability. The adhesive sheet 10 is, for example, an optical adhesive sheet disposed at a light passing portion of a display panel. Examples of the display panel include a liquid crystal display panel and an organic EL display panel. The display panel has a laminated structure including elements such as a pixel panel, a polarizing film, a touch panel, and a cover glass. The adhesive sheet 10 is used, for example, in the manufacturing process of the display panel to bond elements included in the laminated structure.

[0025] The adhesive sheet 10 has at least one conformable step d of 50 μm or more in the step conformability test described below, and the ratio (d / D) of the conformable step d to the thickness D of the adhesive sheet 10 is 0.4 or more and 0.8 or less.

[0026] Step-following test: First, a glass plate (length 100 mm x width 50 mm) having a first surface and a second surface opposite to the first surface, a polyethylene terephthalate film (length 100 mm x width 50 mm), and a sample sheet (length 75 mm x width 45 mm) of the adhesive sheet 10 are prepared (first step). A printed layer having a thickness h of 50 μm or more is formed on the first surface of the glass plate around the entire edge of the glass plate. The printed layer is formed in a range of 15 mm inward from each end of the glass plate in the length direction of the glass plate, and is formed in a range of 5 mm inward from each end of the glass plate in the width direction of the glass plate.

[0027] Next, the first surface side of the glass plate and the polyethylene terephthalate film are bonded in the thickness direction via a sample sheet (adhesive sheet 10) arranged in the center of the glass plate in the length direction and width direction to obtain a bonded body (first bonded body) (second step). FIG. 2 shows the positional relationship between the glass plate 31, the sample sheet 32 ​​of the adhesive sheet 10, and the printed layer 33 in this bonded body. Specifically, the printed layer 33 is formed on one surface of the glass plate 31 in the thickness direction, all around the edge of the glass plate 31. The printed layer 33 is formed in a range of 15 mm inward from each end of the glass plate 31 in the length direction L1, and in a range of 5 mm inward from each end of the glass plate 31 in the width direction L2 (the printed layer 33 is shown with hatching in FIG. 2). The sample sheet 32 ​​is attached to the center of one surface of the glass plate 31 in the thickness direction, and is in contact with the printed layer 33 all around the edge of the sheet. That is, the printed layer 33 on the glass plate 31 was sandwiched between the glass plate 31 and the sample sheet 32 ​​within a range of 2.5 mm outward from the inner edge of the printed layer 33 .

[0028] Next, the bonded body is heat-treated under conditions of 50° C., 0.5 MPa, and 15 minutes (third step).

[0029] Next, the sample sheet 32 ​​in the bonded body was irradiated with an integrated light quantity of 3000 mJ / cm 2The resin is then photocured by exposure to ultraviolet light (fourth step).

[0030] Next, the inside of the inner edge of the printed layer 33 is observed from the polyethylene terephthalate film side of the bonded body with a digital microscope at a magnification of 20 (fifth step). If no air bubbles are found in the observed area, the thickness h is determined as the conformable step d (sixth step). The method of the step conformability test is described more specifically below in relation to the examples.

[0031] The adhesive sheet 10 has an adhesive strength B1 of 1.5 MPa or more in the first tensile test described below.

[0032] First tensile test: First, a first alkali glass plate and a second alkali glass plate are bonded in the thickness direction via an adhesive sheet 10 to obtain a bonded body (second bonded body). As shown in Fig. 3, this bonded body W includes a first alkali glass plate 41, an adhesive sheet 10, and a second alkali glass plate 42 in this order in the thickness direction H. The adhesive sheet 10 bonds the first alkali glass plate 41 and the second alkali glass plate. Next, the adhesive sheet 10 is irradiated with an integrated light quantity of 3000 mJ / cm2. 2 The bonded body W is then photocured by irradiating it with ultraviolet light at 50° C., 0.5 MPa, and 15 minutes. The first alkali glass plate 41 and the second alkali glass plate 42 in the bonded body W are then pulled in opposite directions in the thickness direction at 85° C. and a pulling speed of 25 mm / min to measure the adhesive strength B1. The method of the first tensile test is described more specifically below in relation to the examples.

[0033] As described above, the adhesive sheet 10 includes a base polymer, a first photopolymerizable multifunctional compound, and a photopolymerization initiator. Therefore, the adhesive sheet 10 can be attached to a stepped surface of an adherend in a soft state before photocuring (it can be photocured after attachment). Then, as described above, the adhesive sheet 10 before photocuring has at least one conformable step d of 50 μm or more in a step conformability test, and the ratio (d / D) of the conformable step d to the thickness D of the adhesive sheet 10 is 0.4 or more and 0.8 or less. Such an adhesive sheet 10 is suitable for achieving good step conformability when attached to an adherend having a stepped surface.

[0034] In addition, as described above, the adhesive sheet 10 has an adhesive strength B1 (adhesive strength of the adhesive sheet 10 after photocuring) of 1.5 MPa or more in the first tensile test. Such an adhesive sheet 10 is suitable for achieving good bonding reliability (particularly bonding reliability in high temperature ranges) after bonding between adherends.

[0035] Therefore, the pressure-sensitive adhesive sheet 10 is suitable for achieving both the ability to conform to unevenness in the surfaces of adherends when bonding the adherends together and the bonding reliability after bonding the adherends together.

[0036] From the viewpoint of realizing good step conformability in the pressure-sensitive adhesive sheet 10, the ratio (d / D) is preferably 0.45 or more, more preferably 0.48 or more, and even more preferably 0.5 or more. From the viewpoint of suppressing dents and dents in the pressure-sensitive adhesive sheet 10 and suppressing glue extrusion, the ratio (d / D) is preferably 0.7 or less, more preferably 0.65 or less. Methods for adjusting the ratio (d / D) include, for example, selecting the type of base polymer in the pressure-sensitive adhesive sheet 10, adjusting the molecular weight, adjusting the degree of crosslinking, and adjusting the blending amount. Selecting the type of base polymer includes adjusting the composition of the monomers that form the base polymer.

[0037] From the viewpoint of ensuring the bonding reliability in a high temperature range after bonding between adherends by the pressure-sensitive adhesive sheet 10, the adhesive strength B1 is preferably 1.7 MPa or more, more preferably 1.9 MPa or more, and even more preferably 2.1 MPa or more. The adhesive strength B1 is, for example, 10 MPa or less, 7 MPa or less, or 5 MPa or less. Examples of methods for adjusting the adhesive strength B1 include selecting the type of base polymer in the pressure-sensitive adhesive sheet 10, adjusting the molecular weight, adjusting the degree of crosslinking, and adjusting the blending amount. The selection of the type of base polymer includes adjusting the composition of the monomer that forms the base polymer. Examples of methods for adjusting the adhesive strength B1 include selecting the type of components other than the base polymer in the pressure-sensitive adhesive sheet 10, and adjusting the blending amount of the components. Examples of the components include a first photopolymerizable multifunctional compound, a photopolymerization initiator, a silane coupling agent, and an oligomer. The above-mentioned adjustment methods are also applicable to the adhesive strengths B2 and B3 described below.

[0038] From the viewpoint of ensuring the bonding reliability in the normal temperature range after bonding between adherends by the pressure-sensitive adhesive sheet 10, the adhesive strength B2 in the second tensile test is preferably 4.9 MPa or more, more preferably 5.1 MPa or more, and even more preferably 5.3 MPa or more. The second tensile test is carried out in the same manner as the first tensile test, except that the measurement temperature is 25°C instead of 85°C. More specifically, the method of the second tensile test is as described later in the examples. The adhesive strength B2 is, for example, 15 MPa or less, 12 MPa or less, or 10 MPa or less. In addition, from the viewpoint of ensuring the above-mentioned bonding reliability, the ratio (B2 / B1) of the adhesive strength B2 (25°C) to the adhesive strength B1 (85°C) is preferably 2.0 or more, more preferably 2.2 or more, and also preferably 3.5 or less, more preferably 3.2 or less, and even more preferably 2.9 or less.

[0039] From the viewpoint of ensuring the bonding reliability in a low temperature range after bonding between adherends by the pressure-sensitive adhesive sheet 10, the adhesive strength B3 in the third tensile test is preferably 7.7 MPa or more, more preferably 7.9 MPa or more, and even more preferably 8.0 MPa or more. The third tensile test is carried out in the same manner as the first tensile test, except that the measurement temperature is -20°C instead of 85°C. More specifically, the method of the third tensile test is as described later in the examples. The adhesive strength B3 is, for example, 20 MPa or less, 17 MPa or less, or 15 MPa or less. In addition, from the viewpoint of ensuring the above-mentioned bonding reliability, the ratio (B3 / B1) of the adhesive strength B3 (-20°C) to the adhesive strength B1 (85°C) is preferably 3.0 or more, more preferably 2.2 or more, and also preferably 4.5 or less, more preferably 4.2 or less.

[0040] In this embodiment, the base polymer in the adhesive sheet 10 is a photopolymerization product of a monomer component and a second photopolymerizable multifunctional compound. Photopolymerization is a polymerization method in which a polymerization reaction of a polymerizable component is advanced by irradiation with active energy rays such as ultraviolet light. A photopolymerization product is a product formed by such a polymerization method. In this embodiment, the monomer component is a monofunctional monomer. The second photopolymerizable multifunctional compound is a crosslinking agent in the base polymer. The base polymer is, for example, a photopolymerization product of a partial polymer (including an unreacted monomer component) formed by photopolymerization of a monomer component and a second photopolymerizable multifunctional compound (crosslinking agent).

[0041] Such a base polymer includes a photopolymerized polymer (first photopolymerized polymer) having a crosslinked structure. The crosslinked structure in the first photopolymerized polymer is a structure in which linear structures of units derived from a monofunctional monomer are crosslinked by units derived from a crosslinking agent. The base polymer may include a photopolymerized polymer (second photopolymerized polymer) that does not have such a crosslinked structure. The second photopolymerized polymer is a polymer of a monofunctional monomer.

[0042] The base polymer is preferably an acrylic polymer. The acrylic polymer is a copolymer of polymerizable components containing 50% by mass or more of an alkyl (meth)acrylate ester. "(Meth)acrylic" means acrylic and / or methacrylic.

[0043] The (meth)acrylic acid alkyl ester is preferably a (meth)acrylic acid alkyl ester having an alkyl group having a carbon number of 1 to 20. The (meth)acrylic acid alkyl ester may have a linear or branched alkyl group, or may have a cyclic alkyl group (alicyclic alkyl group).

[0044] Examples of linear or branched (meth)acrylic acid alkyl esters include methyl (meth)acrylate, ethyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, s-butyl (meth)acrylate, t-butyl (meth)acrylate, pentyl (meth)acrylate, isopentyl (meth)acrylate, neopentyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, n-octyl (meth)acrylate, isooctyl (meth)acrylate, nonyl (meth)acrylate, isononyl (meth)acrylate,

[0043] Examples of suitable acrylates include n-decyl (meth)acrylate, isodecyl (meth)acrylate, undecyl (meth)acrylate, dodecyl (meth)acrylate (i.e., lauryl (meth)acrylate), n-tridecyl (meth)acrylate, isotridecyl (meth)acrylate, tetradecyl (meth)acrylate, isotetradecyl (meth)acrylate, pentadecyl (meth)acrylate, cetyl (meth)acrylate, heptadecyl (meth)acrylate, n-octadecyl (meth)acrylate (i.e., n-stearyl (meth)acrylate), isooctadecyl (meth)acrylate (i.e., isostearyl (meth)acrylate), and nonadecyl (meth)acrylate.

[0045] Examples of the (meth)acrylic acid alkyl ester having an alicyclic alkyl group include (meth)acrylic acid cycloalkyl ester, (meth)acrylic acid alkyl ester having a bicyclic aliphatic hydrocarbon ring, and (meth)acrylic acid alkyl ester having a tricyclic or higher aliphatic hydrocarbon ring. Examples of the (meth)acrylic acid cycloalkyl ester include (meth)acrylic acid cyclopentyl, (meth)acrylic acid cyclohexyl, (meth)acrylic acid cycloheptyl, and (meth)acrylic acid cyclooctyl. Examples of the (meth)acrylic acid alkyl ester having a bicyclic aliphatic hydrocarbon ring include (meth)acrylic acid isobornyl. Examples of (meth)acrylic acid alkyl esters having three or more aliphatic hydrocarbon rings include dicyclopentanyl (meth)acrylate, dicyclopentanyloxyethyl (meth)acrylate, tricyclopentanyl (meth)acrylate, 1-adamantyl (meth)acrylate, 2-methyl-2-adamantyl (meth)acrylate, and 2-ethyl-2-adamantyl (meth)acrylate.

[0046] The (meth)acrylic acid alkyl esters may be used alone or in combination of two or more kinds.

[0047] The proportion of the (meth)acrylic acid alkyl ester in the monomer components is preferably 60% by mass or more, more preferably 70% by mass or more, and even more preferably 75% by mass or more, from the viewpoint of appropriately exhibiting basic properties such as adhesiveness in the adhesive sheet 10. This proportion is, for example, 99.9% by mass or less, 99.5% by mass or less, or 99% by mass or less.

[0048] The monomer component may include a copolymerizable monomer that is copolymerizable with the (meth)acrylic acid alkyl ester. Examples of the copolymerizable monomer include a polar group-containing monomer. Examples of the polar group-containing monomer include a hydroxy group-containing monomer, a carboxy group-containing monomer, and a monomer having a nitrogen atom-containing ring. The polar group-containing monomer is useful for modifying the acrylic polymer, such as ensuring the cohesive force of the acrylic polymer.

[0049] Examples of the hydroxyl group-containing monomer include 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 8-hydroxyoctyl (meth)acrylate, 10-hydroxydecyl (meth)acrylate, and 12-hydroxylauryl (meth)acrylate. The hydroxyl group-containing monomer is preferably at least one selected from the group consisting of 2-hydroxyethyl acrylate and 4-hydroxybutyl acrylate.

[0050] The proportion of the hydroxy group-containing monomer in the monomer components is preferably 1% by mass or more, more preferably 5% by mass or more, and even more preferably 8% by mass or more, from the viewpoint of ensuring the cohesive strength of the pressure-sensitive adhesive sheet 10. From the viewpoint of adjusting the polarity of the acrylic polymer (related to the compatibility between the various additive components in the pressure-sensitive adhesive sheet 10 and the acrylic polymer), this proportion is preferably 30% by mass or less, more preferably 20% by mass or less, and even more preferably 15% by mass or less.

[0051] Examples of carboxy group-containing monomers include acrylic acid, methacrylic acid, carboxyethyl acrylate, carboxypentyl acrylate, itaconic acid, maleic acid, fumaric acid, crotonic acid, and isocrotonic acid.

[0052] The proportion of the carboxyl group-containing monomer in the polymerizable component is preferably 1% by mass or more, more preferably 3% by mass or more, and even more preferably 5% by mass or more, from the viewpoints of ensuring the cohesive strength of the pressure-sensitive adhesive sheet 10 and ensuring the adhesive strength to the adherend in the pressure-sensitive adhesive sheet 10. From the viewpoints of adjusting the glass transition temperature of the acrylic polymer and avoiding the risk of corrosion of the adherend by acid, this proportion is preferably 20% by mass or less, and more preferably 10% by mass or less.

[0053] Examples of monomers having a nitrogen atom-containing ring include N-vinyl-2-pyrrolidone, N-methylvinylpyrrolidone, N-vinylpyridine, N-vinylpiperidone, N-vinylpyrimidine, N-vinylpiperazine, N-vinylpyrazine, N-vinylpyrrole, N-vinylimidazole, N-vinyloxazole, N-(meth)acryloyl-2-pyrrolidone, N-(meth)acryloylpiperidine, N-(meth)acryloylpyrrolidine, N-vinylmorpholine, N-vinyl-3-morpholinone, N-vinyl-2-caprolactam, N-vinyl-1,3-oxazin-2-one, N-vinyl-3,5-morpholinedione, N-vinylpyrazole, N-vinylisoxazole, N-vinylthiazole, N-vinylisothiazole, and acryloylmorpholine. The monomer having a nitrogen atom-containing ring is preferably at least one selected from the group consisting of N-vinyl-2-pyrrolidone and acryloylmorpholine.

[0054] The proportion of the monomer having a nitrogen atom-containing ring in the polymerizable component is preferably 1% by mass or more, more preferably 5% by mass or more, and even more preferably 8% by mass or more, from the viewpoints of ensuring the cohesive strength of the pressure-sensitive adhesive sheet and the adhesive strength of the pressure-sensitive adhesive sheet to the adherend. The proportion is preferably 30% by mass or less, more preferably 20% by mass or less, from the viewpoints of adjusting the glass transition temperature of the acrylic polymer and adjusting the polarity of the acrylic polymer (related to the compatibility of various additive components in the pressure-sensitive adhesive sheet with the acrylic polymer).

[0055] The monomer component preferably contains a monomer (high Me monomer) having a homopolymer entanglement point molecular weight Me of 30,000 or more. That is, the base polymer is preferably a photopolymer of a monomer component containing a monomer having a homopolymer entanglement point molecular weight Me of 30,000 or more and a second photopolymerizable polyfunctional compound. Such a base polymer has a lower degree of entanglement and is therefore more flexible than a polymer of the same kind having the same weight average molecular weight and crosslinking degree and not containing a monomer having an entanglement point molecular weight Me of 30,000 or more. That is, the base polymer is suitable for achieving both flexibility and high molecular weight and high crosslinking degree. The high flexibility of the base polymer helps to realize good step-following ability in the adhesive sheet 10 before photocuring. The high molecular weight and crosslinking degree of the base polymer helps to realize good bonding reliability in the adhesive sheet 10 after photocuring that bonds between adherends.

[0056] Examples of high Me monomers include (meth)acrylic acid alkyl esters with Me of 30,000 or more, and copolymerizable monomers with Me of 30,000 or more that are copolymerizable with (meth)acrylic acid alkyl esters. Examples of (meth)acrylic acid alkyl esters with Me of 30,000 or more include (meth)acrylic acid alkyl esters with linear alkyl groups (linear alkyl (meth)acrylates), (meth)acrylic acid alkyl esters with branched alkyl groups (branched alkyl (meth)acrylates), and (meth)acrylic acid alkyl esters with alicyclic alkyl groups (alicyclic alkyl (meth)acrylates). Examples of copolymerizable monomers with Me of 30,000 or more include aromatic ring-containing monomers.

[0057] The high Me monomer is preferably at least one selected from the group consisting of a linear alkyl (meth)acrylate, a branched alkyl (meth)acrylate, an alicyclic alkyl (meth)acrylate, and an aromatic ring-containing monomer.

[0058] Examples of linear alkyl (meth)acrylates as high Me monomers include hexyl methacrylate (Me33800), n-octyl acrylate (Me39400), n-octyl methacrylate (Me47100), n-decyl methacrylate (Me60900), lauryl acrylate (Me39000), lauryl methacrylate (Me80100), n-tridecyl methacrylate (Me89200), n-octadecyl acrylate (Me14700), and n-octadecyl methacrylate (Me215000). Examples of branched alkyl (meth)acrylates as high Me monomers include 2-ethylhexyl acrylate (Me39000) and isooctadecyl acrylate (Me14700). Examples of alicyclic alkyl (meth)acrylates as high Me monomers include cyclohexyl methacrylate (Me33900) and 4-t-butylcyclohexyl methacrylate (Me48400). Examples of aromatic ring-containing monomers as high Me monomers include benzyl acrylate (Me36000), phenyl methacrylate (Me44300), 4-t-butylphenyl methacrylate (Me69700), 4-chlorophenyl acrylate (Me63000), 4-chlorophenyl methacrylate (Me55100), 4-biphenyl methacrylate (Me96000), and triphenylmethyl methacrylate (Me203000). Examples of high Me monomers include 2-cyanoethyl acrylate (Me30000). The method for measuring the molecular weight between entanglement points is described, for example, in "Kobunshi Ronbunshu" (Vol. 52, No. 3, pp. 187-193, March, 1995) and "Polymer Engineering & Science" (Volume 30, Issue 13, p. 753-761).

[0059] The molecular weight Me between entanglement points of the high Me monomer is preferably 35,000 or more, more preferably 38,000 or more, from the viewpoint of achieving both the ability of the adhesive sheet 10 before photocuring to conform to steps on the surface of the adherends when bonding between the adherends, and the bonding reliability of the adhesive sheet 10 after photocuring between the adherends, and is also preferably 300,000 or less, more preferably 250,000 or less, and even more preferably 200,000 or less.

[0060] From the viewpoint of achieving both the above-mentioned step-following ability and bonding reliability, the proportion of high-Me monomers in the monomer components is preferably 5 mass% or more, more preferably 8 mass% or more, even more preferably 10 mass% or more, and is preferably 50 mass% or less, more preferably 40 mass% or less, even more preferably 35 mass% or less.

[0061] The monomer component may contain a monomer (low Me monomer) having a homopolymer interentanglement molecular weight Me of less than 30000. From the viewpoint of appropriately expressing basic properties such as adhesiveness in the pressure-sensitive adhesive sheet 10, the interentanglement molecular weight Me of the low Me monomer is preferably 10000 or more, more preferably 14000 or more, and is preferably less than 30000, more preferably 25000 or less, even more preferably 20000 or less, and even more preferably 17000 or less.

[0062] From the viewpoint of achieving both the above-mentioned step-following ability and bonding reliability, the proportion of low-Me monomers in the monomer components is preferably 50 mass% or more, more preferably 60 mass% or more, even more preferably 65 mass% or more, and is preferably 95 mass% or less, more preferably 92 mass% or less, even more preferably 90 mass% or less.

[0063] The monomer components preferably include a (meth)acrylic acid alkyl ester as a high Me monomer (for example, selected from the above (meth)acrylic acid alkyl esters), a (meth)acrylic acid alkyl ester as a low Me monomer, a monomer having a nitrogen atom-containing ring, and a hydroxyl group-containing monomer. The (meth)acrylic acid alkyl ester as a high Me monomer is preferably a (meth)acrylic acid alkyl ester having 7 to 15 carbon atoms. The (meth)acrylic acid alkyl ester as a low Me monomer is preferably a (meth)acrylic acid alkyl ester having 1 to 6 carbon atoms. The monomer components more preferably include 2-ethylhexyl acrylate (high Me monomer), n-butyl acrylate (low Me monomer), N-vinyl-2-pyrrolidone (NVP), acryloylmorpholine (ACMO), and 4-hydroxybutyl acrylate (4HBA).

[0064] The second photopolymerizable polyfunctional compound (crosslinking agent) may, for example, be a polyfunctional oligomer or a polyfunctional monomer.

[0065] Examples of polyfunctional oligomers include urethane acrylate oligomers (oligomers having a urethane skeleton and two or more acryloyl groups), epoxy acrylate oligomers (oligomers having an epoxy skeleton and two or more acryloyl groups), and silicone acrylate oligomers (oligomers having a siloxane skeleton and two or more acryloyl groups). Commercially available urethane acrylate oligomers include Art Resin UN-333, UN-350, UN-353, UN-5500, and UN-5590 manufactured by Negami Chemical Industries Co., Ltd.

[0066] From the viewpoint of compatibility between the base polymer and the polyfunctional oligomer, the weight average molecular weight (Mw) of the polyfunctional oligomer is preferably 5000 or more, and preferably 20000 or less, more preferably 15000 or less. The weight average molecular weight is measured by gel permeation chromatography (GPC) and calculated in terms of polystyrene.

[0067] The polyfunctional monomer may be, for example, a polyfunctional (meth)acrylate containing two or more ethylenically unsaturated double bonds in one molecule. As the polyfunctional monomer, a polyfunctional (meth)acrylate is preferable from the viewpoint of easily introducing a crosslinked structure by photopolymerization. As the polyfunctional (meth)acrylate, the polyfunctional (meth)acrylate described later in relation to the first photopolymerizable polyfunctional compound may be mentioned.

[0068] The second photopolymerizable multifunctional compound may be used alone or in combination of two or more kinds. The second photopolymerizable multifunctional compound is preferably a multifunctional oligomer, more preferably a urethane acrylate oligomer.

[0069] The amount of the second photopolymerizable multifunctional compound per 100 parts by mass of the monomer component is preferably 0.1 parts by mass or more, more preferably 0.3 parts by mass or more, and even more preferably 0.5 parts by mass or more, from the viewpoint of realizing good bonding reliability in the photocured adhesive sheet 10 that bonds between adherends. The amount of the second photopolymerizable multifunctional compound per 100 parts by mass of the monomer component is preferably 2.0 parts by mass or less, more preferably 1.0 parts by mass or less, and even more preferably 0.8 parts by mass or less, from the viewpoint of ensuring softness and realizing good step conformability in the adhesive sheet 10 before photocuring.

[0070] The base polymer can be formed by photopolymerizing the polymerizable component containing the above-mentioned monomer component (monofunctional monomer) and the second photopolymerizable multifunctional compound. For example, photopolymerization by ultraviolet irradiation can be used as the photopolymerization. The polymerizable components (monofunctional monomer, second photopolymerizable multifunctional compound) may be polymerized at once or in multiple stages. In the multistage polymerization method, first, the monofunctional monomer is polymerized (preliminary polymerization), thereby preparing a prepolymer composition containing a partial polymer (a mixture of a polymer with a low degree of polymerization and an unreacted monofunctional monomer). Next, the second photopolymerizable multifunctional compound as a crosslinking agent is added to the prepolymer composition, and then a polymerization reaction is allowed to proceed in a reaction system containing the partial polymer and the second photopolymerizable multifunctional compound (main polymerization). A photopolymerization initiator is used as the polymerization initiator.

[0071] Examples of the photopolymerization initiator include a radical photopolymerization initiator, a cationic photopolymerization initiator, and an anionic photopolymerization initiator.

[0072] Examples of the radical photopolymerization initiator include an acylphosphine oxide photopolymerization initiator, a benzoin ether photopolymerization initiator, an acetophenone photopolymerization initiator, an α-ketol photopolymerization initiator, an aromatic sulfonyl chloride photopolymerization initiator, a photoactive oxime photopolymerization initiator, a benzoin photopolymerization initiator, a benzyl photopolymerization initiator, a benzophenone photopolymerization initiator, a ketal photopolymerization initiator, and a thioxanthone photopolymerization initiator.

[0073] Examples of acylphosphine oxide photopolymerization initiators include bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide, bis(2,4,6-trimethylbenzoyl)-2,4-di-n-butoxyphenylphosphine oxide, 2,4,6-trimethylbenzoyldiphenylphosphine oxide, and bis(2,6-dimethoxybenzoyl)-2,4,4-trimethylpentylphosphine oxide. Examples of benzoin ether photopolymerization initiators include benzoin methyl ether, benzoin ethyl ether, benzoin propyl ether, benzoin isopropyl ether, benzoin isobutyl ether, and 2,2-dimethoxy-2-phenylacetophenone. Examples of acetophenone photopolymerization initiators include 2,2-diethoxyacetophenone, 1-hydroxycyclohexylphenyl ketone, 4-phenoxydichloroacetophenone, and 4-(t-butyl)dichloroacetophenone. Examples of α-ketol photoinitiators include 2-methyl-2-hydroxypropiophenone and 1-[4-(2-hydroxyethyl)phenyl]-2-methylpropan-1-one. Examples of aromatic sulfonyl chloride photoinitiators include 2-naphthalenesulfonyl chloride. Examples of photoactive oxime photoinitiators include 1-phenyl-1,1-propanedione-2-(o-ethoxycarbonyl)-oxime. Examples of benzoin photoinitiators include benzoin. Examples of benzyl photoinitiators include benzil. Examples of benzophenone photoinitiators include benzophenone, benzoylbenzoic acid, 3,3'-dimethyl-4-methoxybenzophenone, and polyvinylbenzophenone. Examples of ketal photoinitiators include benzyl dimethyl ketal. Examples of the thioxanthone photopolymerization initiator include thioxanthone, 2-chlorothioxanthone, 2-methylthioxanthone, 2,4-dimethylthioxanthone, isopropylthioxanthone, 2,4-diisopropylthioxanthone, and dodecylthioxanthone. The photopolymerization initiator may be used alone or in combination of two or more kinds.The photopolymerization initiator is preferably at least one selected from the group consisting of bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide, 2,2-dimethoxy-2-phenylacetophenone, and 1-hydroxycyclohexyl phenyl ketone.

[0074] The amount of photopolymerization initiator (first photopolymerization initiator) used in the preliminary polymerization (total amount of multiple photopolymerization initiators when multiple photopolymerization initiators are used) is, for example, 0.02 parts by mass or more, preferably 0.04 parts by mass or more, more preferably 0.06 parts by mass or more, and for example, 1 part by mass or less, preferably 0.5 parts by mass or less, more preferably 0.2 parts by mass or less, and even more preferably 0.1 parts by mass or less, relative to 100 parts by mass of the monomer component. The amount of photopolymerization initiator (second photopolymerization initiator) used in the main polymerization (total amount of multiple photopolymerization initiators when multiple photopolymerization initiators are used) is, for example, 0.1 parts by mass or more, preferably 0.2 parts by mass or more, more preferably 0.3 parts by mass or more, and for example, 2 parts by mass or less, preferably 1 part by mass or less, and more preferably 0.8 parts by mass or less, relative to 100 parts by mass of the monomer component.

[0075] The weight average molecular weight (Mw) of the base polymer is preferably 500,000 or more, more preferably 650,000 or more, and even more preferably 800,000 or more, from the viewpoint of ensuring the cohesive force in the pressure-sensitive adhesive sheet 10. The weight average molecular weight of the base polymer is preferably 1,200,000 or less, more preferably 1,000,000 or less, and even more preferably 800,000 or less, from the viewpoint of ensuring the step-following ability of the pressure-sensitive adhesive sheet 10. The weight average molecular weight of the base polymer is measured by gel permeation chromatography (GPC) and calculated in terms of polystyrene. The method for measuring the Mw of the base polymer is specifically as described below in the examples.

[0076] From the viewpoint of ensuring sufficient softness in the pressure-sensitive adhesive sheet 10 before photocuring, the glass transition temperature (Tg) of the base polymer is preferably 0° C. or lower, more preferably −20° C. or lower, even more preferably −40° C. or lower, and even more preferably −45° C. or lower. The glass transition temperature is, for example, −80° C. or higher.

[0077] The glass transition temperature of the base polymer may be determined by the following Fox formula (theoretical value). The Fox formula is a relational expression between the glass transition temperature Tg of a polymer and the glass transition temperature Tgi of a homopolymer of a monomer constituting the polymer. In the following Fox formula, Tg represents the glass transition temperature (°C) of a polymer, Wi represents the weight fraction of a monomer i constituting the polymer, and Tgi represents the glass transition temperature (°C) of a homopolymer formed from the monomer i. The glass transition temperature of a homopolymer may be determined by a literature value. For example, the glass transition temperatures of various homopolymers are listed in "Polymer Handbook" (4th edition, John Wiley & Sons, Inc., 1999). On the other hand, the glass transition temperature of a homopolymer of a monomer may be determined by a method specifically described in JP-A-2007-51271.

[0078] Examples of the first photopolymerizable multifunctional compound in the adhesive sheet 10 include a multifunctional monomer and a multifunctional oligomer.

[0079] Examples of the polyfunctional monomer include polyfunctional (meth)acrylates, such as difunctional (meth)acrylates, trifunctional (meth)acrylates, and tetrafunctional or higher polyfunctional (meth)acrylates.

[0080] Examples of bifunctional (meth)acrylates include ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, tetraethylene glycol dimethacrylate, 1,6-hexanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, glycerin di(meth)acrylate, neopentyl glycol di(meth)acrylate, stearic acid modified pentaerythritol di(meth)acrylate, dicyclopentenyl diacrylate, di(meth)acryloyl isocyanurate, and ethoxylated bisphenol A diacrylate (BPAEODE).

[0081] Examples of trifunctional (meth)acrylates include trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, and tris(acryloyloxyethyl)isocyanurate.

[0082] Examples of tetrafunctional or higher polyfunctional (meth)acrylates include ditrimethylolpropane tetra(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol monohydroxypenta(meth)acrylate, alkyl-modified dipentaerythritol pentaacrylate, and dipentaerythritol hexa(meth)acrylate.

[0083] Examples of the polyfunctional oligomer include the polyfunctional oligomers described above for the second photopolymerizable polyfunctional compound.

[0084] The first photopolymerizable multifunctional compound may be used alone or in combination of two or more kinds.

[0085] The first photopolymerizable multifunctional compound is preferably at least one selected from the group consisting of difunctional (meth)acrylates and trifunctional (meth)acrylates, and more preferably at least one selected from the group consisting of BPAEODE and trimethylolpropane triacrylate (TMPTA).

[0086] The content of the first photopolymerizable multifunctional compound in the adhesive sheet 10 (the total content when the adhesive sheet 10 contains a plurality of first photopolymerizable multifunctional compounds) is preferably 0.5 parts by mass or more, more preferably 2 parts by mass or more, and even more preferably 5 parts by mass or more per 100 parts by mass of the base polymer, from the viewpoint of ensuring good bonding reliability after photocuring in the adhesive sheet 10. The content of the first photopolymerizable multifunctional compound in the adhesive sheet 10 is preferably 20 parts by mass or less, more preferably 15 parts by mass or less, and even more preferably 10 parts by mass or less per 100 parts by mass of the base polymer, from the viewpoint of ensuring good bonding reliability after photocuring in the adhesive sheet 10.

[0087] Examples of the photopolymerization initiator (third photopolymerization initiator) in the adhesive sheet 10 include radical photopolymerization initiators, cationic photopolymerization initiators, and anionic photopolymerization initiators, and specifically include the photopolymerization initiators described above with respect to the photopolymerization of the base polymer.

[0088] In order to ensure good photocurability in the adhesive sheet 10, the content of the photopolymerization initiator in the adhesive sheet 10 is preferably 0.1 part by mass or more, more preferably 0.2 parts by mass or more, even more preferably 0.25 parts by mass or more, per 100 parts by mass of the base polymer, and is preferably 3 parts by mass or less, more preferably 1.5 parts by mass or less, and even more preferably 0.5 parts by mass or less.

[0089] The pressure-sensitive adhesive sheet 10 may contain other components, such as an oligomer, an ultraviolet absorbing agent, an antioxidant, a silane coupling agent, and a rust inhibitor.

[0090] When the base polymer is an acrylic polymer, the oligomer is preferably an acrylic oligomer, which is a copolymer of monomer components containing 50% by mass or more of (meth)acrylic acid ester and has a weight average molecular weight of, for example, 1,000 or more and 30,000 or less.

[0091] The acrylic oligomer is preferably a polymer of a monomer component including a (meth)acrylic acid alkyl ester having a chain alkyl group (chain alkyl (meth)acrylate) and a (meth)acrylic acid alkyl ester having an alicyclic alkyl group (alicyclic alkyl (meth)acrylate). Specific examples of these (meth)acrylic acid alkyl esters include the (meth)acrylic acid alkyl esters described above as the polymerizable component of the acrylic polymer.

[0092] As the chain alkyl (meth)acrylate, methyl methacrylate is preferred because it has a high glass transition temperature and excellent compatibility with the base polymer. As the alicyclic alkyl (meth)acrylate, dicyclopentanyl acrylate, dicyclopentanyl methacrylate, cyclohexyl acrylate, and cyclohexyl methacrylate are preferred. That is, the acrylic oligomer is preferably a polymer of monomer components including one or more selected from the group consisting of dicyclopentanyl acrylate, dicyclopentanyl methacrylate, cyclohexyl acrylate, and cyclohexyl methacrylate, and methyl methacrylate.

[0093] The proportion of alicyclic alkyl (meth)acrylate in the monomer component of the acrylic oligomer is preferably 10% by mass or more, more preferably 20% by mass or more, and even more preferably 30% by mass or more. The proportion is preferably 90% by mass or less, more preferably 80% by mass or less, and even more preferably 70% by mass or less. The proportion of chain alkyl (meth)acrylate in the monomer component of the acrylic oligomer is preferably 90% by mass or less, more preferably 80% by mass or less, and even more preferably 70% by mass or less. The proportion is preferably 10% by mass or more, more preferably 20% by mass or more, and even more preferably 30% by mass or more.

[0094] The acrylic oligomer is obtained by polymerizing the monomer components of the acrylic oligomer. Examples of the polymerization method include solution polymerization, bulk polymerization, and emulsion polymerization. The acrylic oligomer is preferably formed by solution polymerization. Examples of the solvent in the solution polymerization include toluene and ethyl acetate. In the polymerization of the acrylic oligomer, a thermal polymerization initiator may be used, and a chain transfer agent may be used for the purpose of adjusting the molecular weight. In this embodiment, after the formation of the acrylic oligomer, low molecular components and solvents are volatilized and removed from the reaction system such as the reaction solution by heating. Examples of the low molecular components include unreacted monomers, chain transfer agents, thermal polymerization initiators, and decomposition products (residues) thereof.

[0095] Examples of the thermal polymerization initiator include azo polymerization initiators and peroxide polymerization initiators. Examples of the azo polymerization initiator include 2,2'-azobisisobutyronitrile, 2,2'-azobis-2-methylbutyronitrile, and 2,2'-azobis(2-methylpropionate)dimethyl. Examples of the peroxide polymerization initiator include dibenzoyl peroxide, t-butyl permaleate, and lauroyl peroxide.

[0096] Chain transfer agents include α-thioglycerol, lauryl mercaptan, glycidyl mercaptan, mercaptoacetic acid, 2-mercaptoethanol, thioglycolic acid, 2-ethylhexyl thioglycolate, 2,3-dimercapto-1-propanol, and α-methylstyrene dimer.

[0097] From the viewpoint of ensuring the adhesive strength of the adhesive sheet 10, the weight average molecular weight (Mw) of the oligomer is preferably 1000 or more, more preferably 1500 or more, even more preferably 2000 or more, and is preferably 30000 or less, more preferably 10000 or less, even more preferably 8000 or less. The weight average molecular weight of the oligomer is measured by gel permeation chromatography (GPC) and calculated in terms of polystyrene. The method for measuring the Mw of the oligomer is specifically described below in the examples.

[0098] The content of the oligomer in the pressure-sensitive adhesive sheet 10 is preferably 0.05 parts by mass or more, more preferably 0.1 parts by mass or more, and even more preferably 0.2 parts by mass or more, per 100 parts by mass of the base polymer, from the viewpoint of ensuring the adhesive strength of the pressure-sensitive adhesive sheet 10. The content of the oligomer in the pressure-sensitive adhesive sheet 10 is preferably 5 parts by mass or less, more preferably 3 parts by mass or less, and even more preferably 1 part by mass or less, per 100 parts by mass of the base polymer, from the viewpoint of ensuring the transparency of the pressure-sensitive adhesive sheet 10.

[0099] Examples of ultraviolet absorbents include triazine-based ultraviolet absorbents, benzotriazole-based ultraviolet absorbents, benzophenone-based ultraviolet absorbents, salicylate-based ultraviolet absorbents, and cyanoacrylate-based ultraviolet absorbents. As ultraviolet absorbents, triazine-based ultraviolet absorbents are preferred because they have high absorption of ultraviolet rays in the wavelength range of 320 to 370 nm and are highly compatible with acrylic polymers. The ultraviolet absorbents may be used alone or in combination of two or more kinds.

[0100] Commercially available triazine-based UV absorbers include, for example, bisethylhexyloxyphenol methoxyphenyl triazine (product name "Tinosorb S", manufactured by BASF), reaction product of 2-(4,6-bis(2,4-dimethylphenyl)-1,3,5-triazin-2-yl)-5-hydroxyphenyl with [(alkyloxy)methyl]oxirane (product name "TINUVIN 400", manufactured by BASF), reaction product of 2-(2,4-dihydroxyphenyl)-4,6-bis-(2,4-dimethylphenyl)-1,3,5-triazine with (2-ethylhexyl)-glycidic acid ester (product name "TINUVIN 405", manufactured by BASF), (2,4-bis[2-hydroxy-4-butoxyphenyl]-6-(2,4-dibutoxyphenyl)-1,3,5-triazine (product name "TINUVIN Examples of suitable phenols include 2-(4,6-diphenyl-1,3,5-triazin-2-yl)-5-[(hexyl)oxy]phenol (product name "TINUVIN 577", manufactured by BASF), 2-(2-hydroxy-4-[1-octyloxycarbonylethoxy]phenyl)-4,6-bis(4-phenylphenyl)-1,3,5-triazine (product name "TINUVIN 479", manufactured by BASF), and 2-(4,6-diphenyl-1,3,5-triazin-2-yl)-5-[2-(2-ethylhexanoyloxy)ethoxy]phenol ("ADK STAB LA-46", manufactured by ADEKA).

[0101] The content of the ultraviolet absorbing agent in the pressure-sensitive adhesive sheet 10 is preferably 0.5 parts by mass or more, more preferably 1 part by mass or more, and even more preferably 3 parts by mass or more, per 100 parts by mass of the base polymer, and is preferably 15 parts by mass or less, more preferably 10 parts by mass or less, and even more preferably 8 parts by mass or less. Such a configuration is preferable from the viewpoint of achieving both the ultraviolet ray blocking function for device protection and the photocurability in the pressure-sensitive adhesive sheet 10.

[0102] Examples of the antioxidant include phenol-based antioxidants, phosphorus-based antioxidants, sulfur-based antioxidants, and amine-based antioxidants. The antioxidants may be used alone or in combination of two or more kinds.

[0103] As the antioxidant, a phenol-based antioxidant is preferably used, more preferably a hindered phenol-based antioxidant is used. Examples of the hindered phenol-based antioxidant include pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] (product name "Irganox 1010", manufactured by BASF) and octadecyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate (product name "Irganox 1076", manufactured by BASF).

[0104] The content of the antioxidant in the pressure-sensitive adhesive sheet 10 is preferably 0.05 parts by mass or more, more preferably 0.1 parts by mass or more, and preferably 3 parts by mass or less, more preferably 2 parts by mass or less, per 100 parts by mass of the base polymer. Such a configuration is preferable from the viewpoint of achieving both suppression of oxidative deterioration of the pressure-sensitive adhesive sheet 10 and photocurability.

[0105] Examples of the silane coupling agent include silane coupling agents containing an epoxy group. Examples of the silane coupling agent containing an epoxy group include 3-glycidoxydialkyldialkoxysilane and 3-glycidoxyalkyltrialkoxysilane. Examples of the 3-glycidoxydialkyldialkoxysilane include 3-glycidoxypropylmethyldimethoxysilane and 3-glycidoxypropylmethyldiethoxysilane. Examples of the 3-glycidoxyalkyltrialkoxysilane include 3-glycidoxypropyltrimethoxysilane and 3-glycidoxypropyltriethoxysilane. As the silane coupling agent, preferably, 3-glycidoxyalkyltrialkoxysilane is used, and more preferably, 3-glycidoxypropyltrimethoxysilane is used. The silane coupling agent may be used alone or in combination of two or more kinds. The content of the silane coupling agent in the pressure-sensitive adhesive sheet 10 is preferably 0.1 part by mass or more, more preferably 0.2 part by mass or more, and preferably 5 parts by mass or less, more preferably 3 parts by mass or less, per 100 parts by mass of the base polymer.

[0106] Examples of the rust inhibitor include benzotriazole compounds, such as 1,2,3-benzotriazole, 5-methylbenzotriazole, 4-methylbenzotriazole, and carboxybenzotriazole.

[0107] The content of the rust inhibitor in the adhesive sheet 10 is preferably 0.05 parts by mass or more, more preferably 0.1 parts by mass or more, and even more preferably 0.15 parts by mass or more, per 100 parts by mass of the base polymer, and is preferably 2 parts by mass or less, more preferably 1 part by mass or less, and even more preferably 0.5 parts by mass or less.

[0108] From the viewpoint of achieving both sufficient adhesion to the adherend and conformability to unevenness, the thickness of the pressure-sensitive adhesive sheet 10 is preferably 80 μm or more, more preferably 90 μm or more, and even more preferably 95 μm or more. From the viewpoint of ease of handling and cutting of the pressure-sensitive adhesive sheet 10, the thickness of the pressure-sensitive adhesive sheet 10 is preferably 500 μm or less, more preferably 400 μm or less, even more preferably 300 μm or less, still more preferably 200 μm or less, and even more preferably 150 μm or less.

[0109] The pressure-sensitive adhesive sheet 10 preferably has a light transmittance R1 of 10% or less at a wavelength of 380 nm, and a light transmittance R2 of 85% or more at a wavelength of 420 nm. Such a configuration is preferable for the pressure-sensitive adhesive sheet 10 to ensure the transparency required for display panel applications while ensuring the protective function of the display panel by blocking ultraviolet rays. From the viewpoint of ensuring the protective function of the pressure-sensitive adhesive sheet 10, the light transmittance R1 is preferably 8% or less, more preferably 6% or less, and even more preferably 5% or less. The light transmittance R1 is, for example, 0.1% or more. From the viewpoint of ensuring the transparency of the pressure-sensitive adhesive sheet 10, the light transmittance R2 is preferably 87% or more, more preferably 89% or more, and even more preferably 90.5% or more. The light transmittance R2 is, for example, 99% or less. The method for measuring the light transmittances R1 and R2 is specifically as described below in the examples.

[0110] The loss tangent tanδ of the pressure-sensitive adhesive sheet 10 at 25°C is preferably 1.2 or more, more preferably 1.3 or more, and even more preferably 1.4 or more at a frequency of 1000 to 10000 Hz, from the viewpoint of ensuring drop impact resistance (shock mitigation) after bonding between adherends by the pressure-sensitive adhesive sheet 10. The frequency of 1000 to 10000 Hz corresponds to the vibration frequency generated in a colliding object by the collision of a freely falling object. The collision is, for example, the collision of a laminate in which adherends are bonded by a pressure-sensitive adhesive sheet with the ground after free fall. Alternatively, the collision is the collision of a freely falling object (metal ball, etc.) with a laminate in which adherends are bonded by a pressure-sensitive adhesive sheet. The loss tangent tanδ of the pressure-sensitive adhesive sheet 10 at 25°C is preferably 1.8 or less, more preferably 1.7 or less, and even more preferably 1.6 or less at a frequency of 1000 to 10000 Hz, from the viewpoint of the handleability and processability of the pressure-sensitive adhesive sheet 10. The loss tangent tanδ of the adhesive sheet can be measured by a dynamic viscoelasticity measuring device. For example, the "Advanced Rheometric Expansion System" manufactured by Rheometric Scientific can be used as the dynamic viscoelasticity measuring device. In the measurement, the measurement mode is a shear mode, the strain amount is 0.3%, the temperature is -50°C to 150°C, and the angular frequency range is 0.01 rad / sec to 100 rad / sec. The measurement method of the loss tangent tanδ is specifically as described later in the examples. The method of adjusting the loss tangent tanδ of the adhesive sheet 10 includes, for example, selecting the type of base polymer in the adhesive sheet 10, adjusting the molecular weight, adjusting the degree of crosslinking, and adjusting the blending amount.

[0111] The loss tangent tanδ1 of the pressure-sensitive adhesive sheet 10 at 25° C. and a frequency of 1000 Hz is preferably 1.2 or more, and more preferably 1.4 or more, from the viewpoint of drop impact resistance (shock mitigation properties) after bonding between adherends by the pressure-sensitive adhesive sheet 10. The loss tangent tanδ1 (25° C., 1000 Hz) is preferably 1.7 or less, and more preferably 1.6 or less.

[0112] From the viewpoint of the drop impact resistance described above, the loss tangent tanδ2 of the pressure-sensitive adhesive sheet 10 at 25° C. and a frequency of 10,000 Hz is preferably 1.3 or more, more preferably 1.4 or more. The loss tangent tanδ2 (25° C., 10,000 Hz) is preferably 1.7 or less, more preferably 1.6 or less.

[0113] From the viewpoint of ensuring the above-mentioned drop impact resistance, the ratio of loss tangent tan δ1 to loss tangent tan δ2 (tan δ1 / tan δ2) is preferably 0.8 or more, more preferably 0.9 or more, and is preferably 1.4 or less, more preferably 1.3 or less.

[0114] The release liner 21 is, for example, a transparent resin film having flexibility. Examples of the material of the release liner 21 include polyester resin, polyolefin resin, polycarbonate resin, polyethersulfone resin, polyarylate resin, melamine resin, polyamide resin, cellulose resin, and polystyrene resin. Examples of the polyester resin include polyethylene terephthalate (PET), polybutylene terephthalate, and polyethylene naphthalate. Examples of the polyolefin resin include polyethylene, polypropylene, and cycloolefin polymer (COP). From the viewpoints of transparency and strength, the material of the release liner 21 is preferably a polyester resin, and more preferably PET.

[0115] The surface of release liner 21 facing adhesive sheet 10 may be release-treated with a release treatment agent. Examples of release treatments include silicone release treatments, long-chain alkyl acrylate release treatments, and fluorine release treatments. From the viewpoint of ease of adjusting the release force from adhesive sheet 10, silicone release treatments are preferred as the release treatment.

[0116] The thickness of release liner 21 is preferably 5 μm or more, more preferably 10 μm or more, and even more preferably 20 μm or more, from the viewpoint of ensuring the protective function for pressure-sensitive adhesive sheet 10. The thickness of release liner 21 is preferably 200 μm or less, more preferably 150 μm or less, and even more preferably 100 μm or less, from the viewpoint of handleability.

[0117] Release liner 22 is a flexible, transparent resin film. Examples of materials for release liner 22 include the materials described above as the materials for release liner 21. From the viewpoints of transparency and strength, the material for release liner 22 is preferably a polyester resin, and more preferably PET.

[0118] In this embodiment, the surface of the release liner 22 facing the adhesive sheet 10 is release-treated with a release treatment agent. Examples of release treatments include silicone release treatments, long-chain alkyl acrylate release treatments, and fluorine release treatments. From the viewpoint of ease of adjusting the release force from the adhesive sheet 10, silicone release treatments are preferred as the release treatment.

[0119] The thickness of release liner 22 is preferably 5 μm or more, more preferably 10 μm or more, and even more preferably 20 μm or more, from the viewpoint of ensuring the protective function for pressure-sensitive adhesive sheet 10. The thickness of release liner 22 is preferably 200 μm or less, more preferably 150 μm or less, and even more preferably 100 μm or less, from the viewpoint of handleability.

[0120] The adhesive sheet 10 can be produced, for example, as follows.

[0121] First, a prepolymer composition is prepared. Specifically, a mixture (liquid) containing the above-mentioned monofunctional monomer for forming the base polymer and a photopolymerization initiator (first photopolymerization initiator) is prepared (prepolymer composition preparation step). Next, the mixture is irradiated with ultraviolet light to photopolymerize a part of the monofunctional monomer in the mixture to obtain a prepolymer composition. Examples of light sources for ultraviolet light irradiation include ultraviolet LED lights, black light lamps, high pressure mercury lamps, and metal halide lamps. In addition, in the ultraviolet light irradiation, a wavelength cut filter for cutting a part of the wavelength range of the light emitted from the light source may be used as necessary. In the ultraviolet light irradiation, the illuminance is, for example, 5 to 200 mW / cm. 2 m, and the cumulative irradiation dose is, for example, 100 to 5000 mJ / cm 2 The ultraviolet irradiation is preferably continued until the viscosity of the composition reaches about 15 to 25 Pa·s. This viscosity is measured using a Brookfield viscometer with a rotor No. 5 at a rotor speed of 10 rpm and a temperature of 30°C. The prepolymer composition contains a photopolymerized product of a monofunctional monomer (the second photopolymerized polymer) and a monofunctional monomer that has not undergone a polymerization reaction (residual monomer). The prepolymer composition does not contain a solvent.

[0122] Next, the second photopolymerizable multifunctional compound (crosslinking agent), the photopolymerization initiator (second photopolymerization initiator), and other components as necessary are added to the prepolymer composition to prepare the adhesive composition (adhesive composition preparation step). Examples of the other components include an additional monofunctional monomer (additional monomer), an antioxidant, a silane coupling agent, and a rust inhibitor.

[0123] Next, as shown in FIG. 4A, a coating film 10A is formed between the release liners 21 and 22' (coating film forming step). Specifically, first, a pressure-sensitive adhesive composition is applied onto the release surface of the release liner 21 to form the coating film 10A. Examples of methods for applying the pressure-sensitive adhesive composition include roll coating, kiss roll coating, gravure coating, reverse coating, roll brushing, spray coating, dip roll coating, bar coating, knife coating, air knife coating, curtain coating, lip coating, and die coating. Next, the release surface of the release liner 22' is bonded onto the coating film 10A on the release liner 21. For example, the same release liner as the release liner 22 can be used as the release liner 22.

[0124] Next, as shown in Fig. 4B, the coating film 10A between the release liners 21 and 22' is irradiated with ultraviolet light to form a base adhesive sheet 10B (base adhesive sheet forming step). During irradiation with ultraviolet light, a photopolymerization reaction proceeds in the coating film in a reaction system containing a monofunctional monomer (residual monomer, additional monomer) and a second photopolymerizable multifunctional compound (crosslinking agent), forming a base polymer.

[0125] Next, as shown in FIG. 4C, release liner 22' (FIG. 4B) is peeled off from base adhesive sheet 10B (peeling step).

[0126] Next, as shown in FIG. 4D, the later-added component is supplied to the base adhesive sheet 10B (later-added component supplying step). Specifically, a later-added component solution (not shown) containing the later-added component and a solvent is applied to the exposed surface of the base adhesive sheet 10B. The later-added component contains the above-mentioned first photopolymerizable multifunctional compound and the above-mentioned photopolymerization initiator (third photopolymerization initiator), and may contain other additives. Examples of the other additives include an ultraviolet absorber and an antioxidant. In this step, for example, the later-added component is allowed to penetrate into the base adhesive sheet 10B from the surface of the base adhesive sheet 10B, and the solvent is evaporated by heating as necessary. Before this step, the base polymer has already had a crosslinked structure to form the base adhesive sheet 10B. Therefore, the orange peel surface is unlikely to be formed on the base adhesive sheet 10B by the evaporation of the solvent in this step (it is not substantially formed). In addition, a photocurable adhesive sheet 10 is formed by the base adhesive sheet 10B and the later-added component. As described above, the amount of the first photopolymerizable multifunctional compound added in this step is preferably 0.5 parts by mass or more, more preferably 2 parts by mass or more, even more preferably 5 parts by mass or more, and even more preferably 7 parts by mass or more per 100 parts by mass of the base polymer, and is preferably 20 parts by mass or less, more preferably 15 parts by mass or less, and even more preferably 10 parts by mass or less.

[0127] Next, as shown in FIG. 4E, another release liner 22 is laminated to the pressure-sensitive adhesive sheet 10 (lamination step).

[0128] In this manner, it is possible to produce adhesive sheet 10 whose adhesive surface is covered and protected by release liners 21, 22. Adhesive sheet 10 formed from a solventless adhesive composition is suitable for reducing the environmental load.

[0129] 5A to 5C show an example of a method of using the adhesive sheet 10. FIG.

[0130] In this method, first, as shown in FIG. 5A, the adhesive sheet 10 is attached to a cover glass 51 (first adherend) (attaching step). The cover glass 51 has a first surface 51a and a second surface 51b opposite to the first surface 51a. A decorative or light-shielding printed layer 52 is formed on the edge of the first surface 51a. The printed layer 52 is provided, for example, around the entire edge of the cover glass 51. The cover glass 51 has a step (printed step) between the first surface 51a and the surface of the printed layer 52. That is, the cover glass 51 is an adherend having a step on its surface. Specifically, in this step, the adhesive sheet 10 before photocuring is attached to an area including the printed layer 52 on the surface 51a of the cover glass 51. FIG. 5A exemplarily illustrates a case where the adhesive sheet 10 before photocuring is attached to the entire surface 51a of the cover glass 51.

[0131] In the lamination process, the adhesive sheet 10, in a soft state before photo-curing, is laminated to the surface with the printed steps of the cover glass 51. In addition, as described above, the adhesive sheet 10 before photo-curing has at least one conformable step d of 50 μm or more in a step conformability test, and the ratio (d / D) of the conformable step d to the thickness D of the adhesive sheet 10 is 0.4 or more and 0.8 or less. With such an adhesive sheet 10, good step conformability can be achieved in the lamination process.

[0132] 5B, the cover glass 51 and a member 53 are bonded via the adhesive sheet 10 before photocuring on the cover glass 51. The member 53 is, for example, a pixel panel for a display panel, a polarizing film, or a touch panel.

[0133] Next, as shown in FIG. 5C, the adhesive sheet 10 is photocured by ultraviolet irradiation. By the ultraviolet irradiation, a photopolymerization reaction of the first photopolymerizable multifunctional compound proceeds in the adhesive sheet 10, and a photopolymerization product of the first photopolymerizable multifunctional compound is formed. Since the photopolymerization reaction proceeds around the base polymer (the first photopolymerization polymer and the second photopolymerization polymer having a crosslinked structure), the photopolymerization product of the first photopolymerizable multifunctional compound is formed while forming an interpenetrating polymer network (IPN) with the base polymer. This makes the adhesive sheet 10 highly elastic (photocuring of the adhesive sheet 10). Examples of light sources for ultraviolet irradiation include ultraviolet LED lights, black lights, high-pressure mercury lamps, and metal halide lamps. In addition, a wavelength cut filter for cutting a part of the wavelength range of the light emitted from the light source may be used in the ultraviolet irradiation. In the ultraviolet irradiation, the illuminance is, for example, 5 to 200 mW / cm. 2 m, and the cumulative irradiation dose is, for example, 50 to 10,000 mJ / cm 2 It is.

[0134] The adhesive sheet 10 is used, for example, as described above. The adhesive sheet 10 has an adhesive strength B1 (adhesive strength of the adhesive sheet 10 after photocuring) of 1.5 MPa or more in a first tensile test. With such an adhesive sheet 10, good bonding reliability can be achieved after the cover glass 51 and the member 53 are bonded together. EXAMPLES

[0135] The present invention will be specifically described below with reference to examples. However, the present invention is not limited to the examples. In addition, the specific numerical values ​​of the blending amounts (contents), physical property values, parameters, etc. described below can be replaced with the upper limit (a numerical value defined as "equal to or less than") or lower limit (a numerical value defined as "equal to or more than") of the blending amounts (contents), physical property values, parameters, etc. corresponding to those described in the above-mentioned "Form for carrying out the invention".

[0136] Preparation of Acrylic Oligomer First, in a reaction vessel equipped with a stirrer, a thermometer, a reflux condenser, and a nitrogen gas inlet tube, a mixture containing 60 parts by mass of dicyclopentanyl methacrylate (DCPMA), 40 parts by mass of methyl methacrylate (MMA), 3.5 parts by mass of α-thioglycerol as a chain transfer agent, and 100 parts by mass of toluene as a polymerization solvent was stirred under a nitrogen atmosphere at 70°C for 1 hour. Next, 0.2 parts by mass of 2,2'-azobisisobutyronitrile (AIBN) as a thermal polymerization initiator was added to the mixture to prepare a reaction solution, which was reacted under a nitrogen atmosphere at 70°C for 2 hours and then at 80°C for 2 hours (polymerization reaction). Next, the reaction solution was heated at 130°C to volatilize and remove toluene, the chain transfer agent, and unreacted monomers. As a result, an acrylic oligomer (solid state) was obtained. The weight average molecular weight of this acrylic oligomer was 5100.

[0137] Example 1 Preparation of Prepolymer Composition In a flask, 71 parts by mass of n-butyl acrylate (BA), 13 parts by mass of N-vinyl-2-pyrrolidone (NVP), 3 parts by mass of acryloylmorpholine (ACMO), and 13 parts by mass of 4-hydroxybutyl acrylate (4HBA) were added with 0.062 parts by mass of two types of first photopolymerization initiators in total, and then the mixture was irradiated with ultraviolet light under a nitrogen atmosphere to polymerize some of the monomer components in the mixture to obtain a prepolymer composition. The molecular weight between the entanglement points of n-butyl acrylate (BA) was 15,000. As the first photopolymerization initiator, 0.031 parts by mass of "Omnirad184" (1-hydroxy-cyclohexyl-phenyl-ketone) manufactured by BASF and 0.031 parts by mass of "Omnirad651" (2,2-dimethoxy-2-phenylacetophenone) manufactured by BASF were used. The ultraviolet light irradiation was continued until the viscosity of the composition reached about 20 Pa·s. This viscosity is a value measured using a Brookfield viscometer with a rotor No. 5 at a rotor rotation speed of 10 rpm and a temperature of 30° C. The obtained prepolymer composition is a partial polymer containing a photopolymerized product (photopolymerized polymer P1a) and a monomer component that has not undergone a polymerization reaction (residual monomer).

[0138] Preparation of Pressure-Sensitive Adhesive Composition Next, 100 parts by mass of the prepolymer composition, 10 parts by mass of 2-ethylhexyl (meth)acrylate (2EHA) as an additional monomer, 3 parts by mass of the above acrylic oligomer, 0.6 parts by mass of urethane acrylate oligomer (UAO) (product name "UN-350", manufactured by Negami Chemical Industries Co., Ltd.) as a second photopolymerizable multifunctional compound, 0.4 parts by mass of a second photopolymerization initiator, 0.5 parts by mass of an antioxidant (product name "Irganox 1010", manufactured by BASF), 0.2 parts by mass of a rust inhibitor (product name "BT-120", 1,2,3-benzotriazole, manufactured by Johoku Chemical Industry Co., Ltd.), and 0.3 parts by mass of a silane coupling agent (product name "KBM-403", manufactured by Shin-Etsu Chemical Co., Ltd.) were mixed to obtain a pressure-sensitive adhesive composition. The molecular weight between the entanglement points of 2EHA is 39,000. The amount of the second photopolymerizable multifunctional compound (crosslinking agent) per 100 parts by mass of the monomer component was 0.55 parts by mass. As the second photopolymerization initiator, BASF's "Omnirad819" (bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide) was used.

[0139] <Preparation of Base Adhesive Sheet> Next, a pressure-sensitive adhesive composition was applied onto the release-treated surface of a first release liner (product name "Diafoil MRF", thickness 75 μm, manufactured by Mitsubishi Chemical Corporation) having a release-treated surface on one side to form a coating film. Next, the release-treated surface of a second release liner (product name "Diafoil MRE", thickness 75 μm, manufactured by Mitsubishi Chemical Corporation) having a release-treated surface on one side was attached onto the coating film on the first release liner. Next, the coating film between the release liners was irradiated with ultraviolet light from the second release liner side, and the coating film was photocured to form a 100 μm-thick pressure-sensitive adhesive layer (ultraviolet light irradiation step). For ultraviolet light irradiation, a black light lamp (wavelength 320 nm to 400 nm, manufactured by Toshiba) was used as the light source, and the illuminance was set to 6.5 mW / cm. 2 The cumulative irradiation dose was 1500 mJ / cm 2In the ultraviolet irradiation step, a photopolymerization reaction proceeds in the coating film in a reaction system containing the above-mentioned residual monomer, additional monomer, and second photopolymerizable multifunctional compound (crosslinking agent), forming a photopolymerized polymer P1b having a crosslinked structure. In addition, since the photopolymerization reaction proceeds around the photopolymerized polymer P1a, the photopolymerized polymer P1b is formed around the photopolymerized polymer P1a. The adhesive layer formed in this step contains such photopolymerized polymer P1a and photopolymerized polymer P1b as the base polymer P1. In this manner, a base adhesive sheet with double-sided release liners (first release liner / base adhesive sheet (thickness 100 μm) / second release liner) was produced.

[0140] Preparation of Post-Added Component Solutions 6.0 parts by mass of trimethylolpropane triacrylate (TMPTA) (product name "Viscoat #295", manufactured by Osaka Organic Chemical Industry Co., Ltd.) as a first photopolymerizable multifunctional compound, and ethoxylated bisphenol A diacrylate (BPAEODE) (product name "ABE-300", manufactured by Shin-Nakamura Chemical Co., Ltd.) as another first photopolymerizable multifunctional compound. A post-addition component solution was prepared by mixing 1.2 parts by mass of the tertiary photopolymerization initiator, 0.3 parts by mass of a third photopolymerization initiator, 7.0 parts by mass of an ultraviolet absorber (trade name "Tinosorb S", manufactured by BASF), and 85.5 parts by mass of ethyl acetate as a solvent (everything in the solution other than the solvent is a post-addition component). "Omnirad819" manufactured by BASF was used as the third photopolymerization initiator. The composition of the post-addition component solution is shown in Table 1. In Table 1, the unit of the blending amount of each component is the relative "parts by mass".

[0141] <Preparation of optical adhesive sheet> First, the second release liner was peeled off from the base adhesive sheet with the release liner described above, and then the post-added component solution was applied to a thickness of 20 μm on the exposed surface of the base adhesive sheet (coating process). A bar coater RDS No. 10 manufactured by RDSPECIALTIES was used for the coating. Next, a drying process was performed for 60 seconds in a dryer at 110°C. The coating process and drying process allowed the post-added components (first photopolymerizable multifunctional compound, third photopolymerization initiator, ultraviolet absorber) to permeate the base adhesive sheet, and also vaporized the solvent. A photocurable optical adhesive sheet was formed by the permeation of the post-added components into the base adhesive sheet. The amount of TMPTA added per 100 parts by mass of the above prepolymer composition was 6.0 parts by mass, the amount of BPAEODE added was 1.2 parts by mass, the amount of the third photopolymerization initiator (Omnirad819) added was 0.3 parts by mass, and the amount of the ultraviolet absorber (Tinosorb S) added was 7.0 parts by mass (in Table 2, the amount per 100 parts by mass of the monomer component for the first photopolymerizable multifunctional compound is shown in parentheses). Next, the release-treated surface of a third release liner (product name "Diafoil MRE", thickness 75 μm, manufactured by Mitsubishi Chemical Corporation) having a release-treated surface on one side was attached to the pressure-sensitive adhesive sheet on the first release liner.

[0142] In this manner, an adhesive sheet with release liner (first release liner / adhesive sheet (thickness 100 μm) / third release liner) of Example 1 was produced. The adhesive sheet is a photocurable optical adhesive sheet containing a base polymer, a first photopolymerizable multifunctional compound (TMPTA, BPAEODE), and a third photopolymerization initiator.

[0143] Example 2 A pressure-sensitive adhesive sheet with a release liner of Example 2 was produced in the same manner as the pressure-sensitive adhesive sheet with a release liner of Example 1, except for the following: In preparing the pressure-sensitive adhesive composition, the blend amount of 2EHA was set to 20 parts by mass.

[0144] Example 3 The pressure-sensitive adhesive sheet with release liner of Example 3 was produced in the same manner as the pressure-sensitive adhesive sheet with release liner of Example 1, except for the following: In preparing the pressure-sensitive adhesive composition, the blend amount of 2EHA was set to 30 parts by mass.

[0145] Example 4 The release-lined adhesive sheet of Example 4 was produced in the same manner as the release-lined adhesive sheet of Example 1, except for the following: In preparing the adhesive composition, the amount of 2EHA was 20 parts by mass; In preparing the post-addition component solution, BPAEODE was not used, and the amount of ethyl acetate was 86.7 parts by mass; In the adhesive sheet of Example 4, the amount of TMPTA added as the second photopolymerizable multifunctional compound was 6.0 parts by mass, and the amount of the third photopolymerization initiator (Omnirad819) added was 0.3 parts by mass, per 100 parts by mass of the prepolymer composition.

[0146] Example 5 The release-lined adhesive sheet of Example 5 was produced in the same manner as the release-lined adhesive sheet of Example 1, except for the following: In the preparation of the adhesive composition, the amount of 2EHA was 20 parts by mass. In the preparation of the post-addition component solution, the amount of TMPTA was 4.0 parts by mass, the amount of BPAEODE was 1.2 parts by mass, and the amount of ethyl acetate was 87.5 parts by mass. In the adhesive sheet of Example 5, the amount of TMPTA added was 4.0 parts by mass, the amount of BPAEODE added was 1.2 parts by mass, and the amount of the third photopolymerization initiator (Omnirad819) added was 0.3 parts by mass per 100 parts by mass of the prepolymer composition.

[0147] Example 6 The release-lined adhesive sheet of Example 6 was produced in the same manner as the release-lined adhesive sheet of Example 1, except for the following: In the preparation of the adhesive composition, the amount of 2EHA was 20 parts by mass. In the preparation of the post-addition component solution, the amount of TMPTA was 2.0 parts by mass, the amount of BPAEODE was 1.2 parts by mass, and the amount of ethyl acetate was 89.5 parts by mass. In the adhesive sheet of Example 6, the amount of TMPTA added was 2.0 parts by mass, the amount of BPAEODE added was 1.2 parts by mass, and the amount of the third photopolymerization initiator (Omnirad819) added was 0.3 parts by mass per 100 parts by mass of the prepolymer composition.

[0148] Comparative Example 1 An adhesive sheet with a release liner of Comparative Example 1 was produced in the same manner as the adhesive sheet with a release liner of Example 1, except for the following: 2EHA was not used in preparing the adhesive composition.

[0149] Comparative Example 2 The release-lined adhesive sheet of Comparative Example 2 was produced in the same manner as the release-lined adhesive sheet of Comparative Example 1, except for the following: In preparing the post-addition component solution, BPAEODE was not used, and the amount of ethyl acetate was 86.7 parts by mass. In the adhesive sheet of Comparative Example 2, the amount of TMPTA added as the second photopolymerizable multifunctional compound per 100 parts by mass of the prepolymer composition was 6.0 parts by mass, and the amount of the third photopolymerization initiator (Omnirad819) added was 0.3 parts by mass.

[0150] Comparative Example 3 A release-lined adhesive sheet of Comparative Example 3 was produced in the same manner as the release-lined adhesive sheet of Comparative Example 1, except for the following: In the preparation of the post-addition component solution, the amount of TMPTA was 4.0 parts by mass, BPAEODE was not used, and the amount of ethyl acetate was 88.7 parts by mass. In the adhesive sheet of Comparative Example 3, the amount of TMPTA added as the second photopolymerizable multifunctional compound was 4.0 parts by mass, and the amount of the third photopolymerization initiator (Omnirad819) added was 0.3 parts by mass per 100 parts by mass of the prepolymer composition.

[0151] Comparative Example 4 The release-lined adhesive sheet of Comparative Example 4 was produced in the same manner as the release-lined adhesive sheet of Comparative Example 1, except for the following: In the preparation of the post-addition component solution, the amount of TMPTA was 2.0 parts by mass, BPAEODE was not used, and the amount of ethyl acetate was 90.7 parts by mass. In the adhesive sheet of Comparative Example 4, the amount of TMPTA added as the second photopolymerizable multifunctional compound was 2.0 parts by mass, and the amount of the third photopolymerization initiator (Omnirad819) added was 0.3 parts by mass per 100 parts by mass of the prepolymer composition.

[0152] Comparative Example 5 The adhesive sheet with release liner of Comparative Example 5 was prepared in the same manner as the adhesive sheet with release liner of Example 1, except for the following: 2EHA was not used in the preparation of the adhesive composition. In the ultraviolet irradiation step for preparing the base adhesive sheet, ultraviolet irradiation (first irradiation) was performed using a black light lamp (wavelength 320 nm to 400 nm, manufactured by Toshiba), followed by ultraviolet irradiation (second irradiation) using an ultraviolet LED light (wavelength 365 nm, manufactured by Quark Technology). In the first irradiation, the illuminance was 6.5 mW / cm. 2 The cumulative irradiation dose was 1500 mJ / cm 2 In the second irradiation, the illuminance was 90 mW / cm 2 The cumulative irradiation dose was 1800 mJ / cm 2 By such ultraviolet irradiation process, a base polymer P2 having a weight average molecular weight (Mw) smaller than that of the above-mentioned base polymer P1 was formed. In addition, in the preparation of the post-addition component solution, BPAEODE was not used, and the amount of ethyl acetate was 86.7 parts by mass. In the pressure-sensitive adhesive sheet of Comparative Example 5, the amount of TMPTA added as the second photopolymerizable multifunctional compound per 100 parts by mass of the prepolymer composition was 6.0 parts by mass, and the amount of the third photopolymerization initiator (Omnirad819) added was 0.3 parts by mass.

[0153] Comparative Example 6 The release-lined adhesive sheet of Comparative Example 6 was prepared in the same manner as the release-lined adhesive sheet of Comparative Example 5, except for the following: In the preparation of the post-addition component solution, the amount of TMPTA was 4.0 parts by mass, BPAEODE was not used, and the amount of ethyl acetate was 88.7 parts by mass. In the adhesive sheet of Comparative Example 6, the amount of TMPTA added as the second photopolymerizable multifunctional compound per 100 parts by mass of the prepolymer composition was 4.0 parts by mass, and the amount of the third photopolymerization initiator (Omnirad819) added was 0.3 parts by mass.

[0154] Comparative Example 7 The release-lined adhesive sheet of Comparative Example 7 was prepared in the same manner as the release-lined adhesive sheet of Comparative Example 5, except for the following: In the preparation of the post-addition component solution, the amount of TMPTA was 2.0 parts by mass, BPAEODE was not used, and the amount of ethyl acetate was 90.7 parts by mass. In the adhesive sheet of Comparative Example 7, the amount of TMPTA added as the second photopolymerizable multifunctional compound was 2.0 parts by mass, and the amount of the third photopolymerization initiator (Omnirad819) added was 0.3 parts by mass per 100 parts by mass of the prepolymer composition.

[0155] <Measurement of weight average molecular weight> The weight average molecular weight (Mw) of each of the above-mentioned acrylic polymer and acrylic oligomer was measured by gel permeation chromatography (GPC) under the following measurement conditions and calculated in terms of polystyrene. A GPC measuring device (product name "HLC-8120GPC", manufactured by Tosoh Corporation) was used for the measurement. The sample solution was prepared as follows. First, a dimethylformamide (DMF) solution (salt added) with a sample concentration of 0.20 mass% was prepared using the acrylic oligomer as a sample, and the DMF solution was left to stand for 20 hours. Next, the DMF solution was filtered through a membrane filter with an average pore size of 0.45 μm, and the filtrate was obtained as a sample solution for molecular weight measurement.

[0156] [GPC measurement conditions] Columns: SuperAWM-H + SuperAW4000 + SuperAW2500, each TSKgel (Tosoh) Column temperature: 40℃ Eluent: DMF solution (salt added) Flow rate: 0.4mL / min Sample injection volume: 40 μL Standard sample: Polystyrene (Agilent) Detector: Differential refractometer (RI)

[0157] <Light transmittance> The light transmittance of each of the pressure-sensitive adhesive sheets of Examples 1 to 6 and Comparative Examples 1 to 7 was measured as follows. First, a sample for measuring the transmittance was prepared. Specifically, after peeling off the third release liner from the pressure-sensitive adhesive sheet, the exposed surface of the pressure-sensitive adhesive sheet was attached to alkali-free glass (manufactured by Matsunami Glass Co., Ltd.), and the release liner was peeled off from the pressure-sensitive adhesive sheet on the glass. This resulted in a sample for measurement. Next, a spectrophotometer (name "U4100", manufactured by Hitachi High-Technologies Corporation) was used to measure the light transmittance of the pressure-sensitive adhesive sheet in the sample. In addition, in this measurement, the measurement results obtained by measuring only the alkali-free glass under the same conditions were used as a baseline. The light transmittance R1 at a wavelength of 380 nm and the light transmittance R2 at a wavelength of 420 nm measured for the pressure-sensitive adhesive sheet are shown in Tables 2 and 3.

[0158] <Step-following ability> The step-conforming ability of each of the pressure-sensitive adhesive sheets of Examples 1 to 6 and Comparative Examples 1 to 7 was examined as follows.

[0159] First, a sample sheet (length 75 mm x width 45 mm) was cut out from the adhesive sheet with a release liner. Next, the third release liner was peeled off from the adhesive sheet in the sample sheet, and the exposed surface of the adhesive sheet was bonded to the center of a PET film (length 100 mm x width 50 mm, thickness 125 μm). In bonding, a roll laminator was used, the pressure between the rolls was set to 0.2 MPa, and the feed speed was set to 100 mm / min. Next, the first release liner was peeled off from the adhesive sheet on the PET film, and the exposed surface of the adhesive sheet was bonded to a glass plate (length 100 mm x width 50 mm, thickness 500 μm) with a printed layer to obtain a bonded body (first bonded body). In bonding, a roll laminator was used, the pressure between the rolls was set to 0.2 MPa, and the feed speed was set to 100 mm / min. FIG. 2 shows the positional relationship between the glass plate 31, the sample sheet 32 ​​(optical adhesive sheet), and the printed layer 33 in this first bonded body. On one surface in the thickness direction of the glass plate 31, a printed layer 33 (black ink layer) of a predetermined thickness (45 μm, 50 μm) is formed around the entire edge of the glass plate 31. The printed layer 33 is formed in a range of 15 mm inward from each end of the glass plate 31 in the length direction L1, and in a range of 5 mm inward from each end of the glass plate 31 in the width direction L2 (the printed layer 33 is shown hatched in FIG. 2). The sample sheet 32 ​​is bonded to the center of one surface in the thickness direction of the glass plate 31, and is in contact with the printed layer 33 around the entire edge of the sheet. That is, the printed layer 33 on the glass plate 31 is sandwiched between the glass plate 31 and the sample sheet 32 ​​in a range of 2.5 mm outward from the inner end of the layer.

[0160] Next, the first bonded body was autoclaved under conditions of 50°C, 0.5 MPa and 15 minutes. Next, the sample sheet 32 ​​on the glass plate 31 was irradiated with ultraviolet light from the glass plate 31 side to photo-cure the sample sheet 32. For the ultraviolet light irradiation, a metal halide lamp was used as the light source, and the illuminance was 300 mW / cm. 2 The cumulative irradiation dose was 3000 mJ / cm 2Then, the vicinity of the inner edge of the printed layer 33 in the first bonded body was observed. Specifically, the inside of the inner edge of the printed layer 33 (the area where the sample sheet 32 ​​should be in close contact with the glass plate 31) was observed with a digital microscope from the PET film side of the first bonded body at an observation magnification of 20. As a result, when the thickness of the printed layer was 45 μm, no air bubbles were confirmed in the observed range in each of the adhesive sheets (thickness 100 μm) of Examples 1 to 6 and Comparative Examples 1 to 7. When the thickness of the printed layer was 50 μm, no air bubbles were confirmed in the observed range in each of the adhesive sheets (thickness 100 μm) of Examples 1 to 6 and Comparative Examples 5 to 7, and air bubbles were confirmed in the observed range in each of the adhesive sheets (thickness 100 μm) of Comparative Examples 1 to 4. That is, for each of the pressure-sensitive adhesive sheets in Examples 1 to 6 and Comparative Examples 5 to 7, the ratio (d / D) of the conformable step d to the thickness D of the pressure-sensitive adhesive sheet was 0.5, and for each of the pressure-sensitive adhesive sheets in Comparative Examples 1 to 4, the ratio (d / D) of the conformable step d to the thickness D of the pressure-sensitive adhesive sheet was 0.45. With regard to the step conformability of the pressure-sensitive adhesive sheet, when the thickness of the printed layer was 50 μm and no air bubbles were observed within the observed range, the sheet was evaluated as "excellent," and when air bubbles were observed, the sheet was evaluated as "poor." These results are shown in Tables 2 and 3.

[0161] Tensile Test For each of the pressure-sensitive adhesive sheets in Examples 1 to 6 and Comparative Examples 1 to 7, the adhesive strength was measured by the following tensile test.

[0162] First, a measurement sample was prepared for each adhesive sheet. In preparing the measurement sample, first, the third release liner of the adhesive sheet piece (10 mm × 10 mm) cut out from the adhesive sheet with release liner was peeled off, and the exposed surface was attached to one of the alkali glass plates (first alkali glass plate). Next, the first release liner was peeled off from the adhesive sheet piece on the alkali glass plate, and the exposed surface was attached to the other alkali glass plate (second alkali glass plate) to bond the glass plates together. This resulted in a bonded body (second bonded body) in which the first alkali glass plate and the second alkali glass plate were bonded in the thickness direction via the adhesive sheet piece. Next, the second bonded body was heat-treated under conditions of a temperature of 50 ° C, a pressure of 0.5 MPa, and 15 minutes, and the adhesive sheet piece was pressed against both glass plates. Next, the adhesive sheet between the glass plates in the second bonded body was photocured by ultraviolet irradiation. For ultraviolet irradiation, a metal halide lamp was used as a light source, and the illuminance was 300 mW / cm. 2 The cumulative irradiation dose was 3000 mJ / cm 2 In this manner, a measurement sample (first alkali glass plate / adhesive sheet piece / second alkali glass plate) was prepared. As shown in Fig. 3, the measurement sample (second bonded body) W includes a first alkali glass plate 41, an adhesive sheet 10, and a second alkali glass plate 42 in this order in the thickness direction H. The adhesive sheet 10 bonds the first alkali glass plate 41 and the second alkali glass plate.

[0163] Next, a test was conducted in which the two alkali glass plates in the measurement sample were pulled in opposite directions in the thickness direction to measure the force required to separate the glass plates (first tensile test). A tensile tester (product name "Autograph AG-50NX plus", manufactured by Shimadzu Corporation) was used for this measurement. In this measurement, the measurement temperature was 85°C, the relative humidity was 55%, and the pulling speed was 25 mm / min. The maximum force measured is shown in Tables 2 and 3 as the adhesive strength B1 (MPa) at 85°C.

[0164] A tensile test was carried out in the same manner as the first tensile test, except that the measurement temperature was 25°C instead of 85°C, and the force required to separate the glass sheets was measured (second tensile test). The maximum force measured is shown in Tables 2 and 3 as adhesive strength B2 (MPa) at 25°C. The ratio of adhesive strength B2 to adhesive strength B1 (B2 / B1) is also shown in Tables 2 and 3.

[0165] A tensile test was carried out in the same manner as in the first tensile test, except that the measurement temperature was -20°C instead of 85°C, and the force required to separate the glass sheets was measured (third tensile test). The maximum force measured is shown in Tables 2 and 3 as adhesive strength B3 (MPa) at -20°C. The ratio of adhesive strength B3 to adhesive strength B1 (B3 / B1) is also shown in Tables 2 and 3.

[0166] Dynamic Viscoelasticity Measurement For each of the pressure-sensitive adhesive sheets of Examples 1 to 6 and Comparative Examples 1 to 7, the dynamic viscoelasticity was measured.

[0167] First, a required number of samples for measurement were prepared for each adhesive sheet. Specifically, first, a plurality of pieces of adhesive sheet cut out from the adhesive sheet were pasted together to prepare a sample sheet with a thickness of about 1 mm. Next, this sheet was punched out to obtain cylindrical pellets (diameter 7.9 mm) as the measurement samples.

[0168] Next, dynamic viscoelasticity measurements were performed on the measurement samples using a dynamic viscoelasticity measuring device (name: Advanced Rheometric Expansion System (ARES) G2, manufactured by TA Instruments). Specifically, the measurement samples were fixed to a 7.9 mm diameter parallel plate fixture of the device, and then measurements were performed. In this measurement, the measurement mode was shear mode, the strain amount was 0.3%, the measurement temperature was in the range of -50°C to 150°C in 5°C increments, and the angular frequency range was 0.01 rad / sec to 100 rad / sec. Next, the analysis software built into the dynamic viscoelasticity measuring device was used to calculate the reference temperature of 25°C and the frequency range of 1.0 x 10 -7 Hz~1×10 9A master curve (synthetic curve) spanning a range of 1000 Hz was synthesized from the measurement data. This resulted in frequency-dependent data for the shear storage modulus G' and loss tangent tanδ (= shear loss modulus G" / shear storage modulus G'). From the obtained data, the loss tangent tanδ1 at a frequency of 1000 Hz, the loss tangent tanδ2 at a frequency of 10000 Hz, and the minimum value Vmin and maximum value Vman of the loss tangent tanδ at frequencies of 1000 to 10000 Hz were read. These values ​​are shown in Tables 2 and 3. The ratio of the loss tangent tanδ1 to the loss tangent tanδ2 (tanδ1 / tanδ2) is also shown in Tables 2 and 3. In addition, the temperature at which the loss tangent tanδ was maximized in the measurement temperature range was read. The value is shown in Tables 2 and 3 as the glass transition temperature Tg (℃) of the pressure-sensitive adhesive sheet.

[0169] <Drop impact resistance> The drop impact resistance of each of the pressure-sensitive adhesive sheets of Examples 1 to 6 and Comparative Examples 1 to 7 was examined as follows.

[0170] First, a bonded body (third bonded body) for evaluation was prepared. Specifically, a rectangular sample sheet (length 75 mm x width 45 mm) was cut out from the adhesive sheet with a release liner. Next, the third release liner was peeled off from the adhesive sheet in the sample sheet, and the exposed surface of the adhesive sheet was bonded to the center of a rectangular first glass plate (length 100 mm x width 75 mm, thickness 500 μm) along its four sides. A roll laminator was used for bonding, with a roll pressure of 0.2 MPa and a feed rate of 100 mm / min. Next, the adhesive sheet on the first glass plate was photocured by ultraviolet irradiation. For ultraviolet irradiation, a metal halide lamp was used as a light source, and the illuminance was 300 mW / cm. 2 The cumulative irradiation dose was 3000 mJ / cm 2Next, the first release liner was peeled off from the adhesive sheet on the first glass plate, and the exposed surface of the adhesive sheet was bonded to the center of a rectangular second glass plate (length 100 mm × width 50 mm, thickness 500 μm) with a printed layer by vacuum pressing (surface pressure 0.3 MPa, pressure 100 Pa) along the four sides to obtain a third bonded body. A printed layer (thickness 30 μm, black ink layer) was formed on one surface in the thickness direction of the second glass plate along the entire edge of the second glass plate. The printed layer was formed in a range of 15 mm inward from each end of the second glass plate in the length direction, and in a range of 5 mm inward from each end of the second glass plate in the width direction. The adhesive sheet was bonded to the center of one surface in the thickness direction of the second glass plate, and was in contact with the printed layer along the entire edge of the sheet. That is, the printed layer on the second glass plate was sandwiched between the second glass plate and the adhesive sheet within a range of 2.5 mm outward from the inner end of the printed layer. Such a third bonded body was then heat-treated (autoclave) under conditions of 50° C., 0.5 MPa and 30 minutes.

[0171] Using the third bonded body prepared as described above, a drop impact resistance test was carried out as follows. First, the bonded body was placed on a predetermined support stand. Specifically, the bonded body was placed on the support stand so that the first glass plate in the bonded body was located on the upper side and both ends in the width direction of the first glass plate were supported from below by the support stand (the lower second glass plate was not in contact with the support stand). Next, the bonded body on the support stand was fixed to the support stand with adhesive tape. Next, the support stand and the bonded body were kept in an environment of -5°C for 24 hours. Next, within 40 seconds after the support stand and the bonded body were returned to a room temperature environment, a metal ball was dropped toward the bonded body on the support stand, and the metal ball collided with the first glass plate of the bonded body. The mass of the metal ball was 30 g, and the drop height of the metal ball was 300 mm. The drop position of the metal ball on the bonded body was a position 10 mm or more away from the printed layer in both the length direction and the width direction. Two tests (tests with different samples) were carried out for each adhesive sheet (n=2). Regarding the drop impact resistance of the adhesive sheet, if peeling between the first and second glass plates did not occur in any of the tests, it was rated as "excellent," if it occurred in only one test, it was rated as "fair," and if it occurred in all tests, it was rated as "poor." The results are shown in Tables 2 and 3.

[0172] [Table 1]

[0173] [Table 2]

[0174] [Table 3] [Explanation of symbols]

[0175] 10 Adhesive sheet (optical adhesive sheet) H Thickness direction 21,22 Release Liner 31 Coverslip 32 Printing layer 33 Materials

Claims

1. An optical adhesive sheet, The composition includes a base polymer, a photopolymerizable multifunctional compound, and a photopolymerization initiator, In the step conformability test described below, the optical adhesive sheet has at least one conformable step d of 50 μm or more, and the ratio of the conformable step d to the thickness D of the optical adhesive sheet is 0.4 to 0.8, An optically adhesive sheet having an adhesive strength B1 of 1.5 MPa or more in the first tensile test described below. Step-following test: First, a glass plate (length 100 mm x width 50 mm) having a first surface and a second surface opposite to the first surface, a polyethylene terephthalate film (length 100 mm x width 50 mm), and a sample sheet (length 75 mm x width 45 mm) of the optical adhesive sheet are prepared. A printed layer having a thickness h of 50 μm or more is formed on the first surface of the glass plate around the entire edge of the glass plate. The printed layer is formed in a range of 15 mm inward from each end of the glass plate in the longitudinal direction of the glass plate, and in a range of 5 mm inward from each end of the glass plate in the width direction of the glass plate. Next, the first surface side of the glass plate and the polyethylene terephthalate film are bonded in the thickness direction via the sample sheet that is positioned at the center of the glass plate in the longitudinal direction and the width direction, to obtain a first bonded body. In the first bonded body, the printed layer was sandwiched between the glass plate and the sample sheet in a range of 2.5 mm outward from the inner edge of the printed layer. Next, the first bonded body is heat-treated under conditions of 50° C., 0.5 MPa and 15 minutes. Next, the sample sheet in the first bonded body is irradiated with an integrated light quantity of 3000 mJ / cm 2 The resin is photocured by exposure to ultraviolet light. Next, the inside of the inner edge of the printed layer from the polyethylene terephthalate film side of the first bonded body is observed with a digital microscope at an observation magnification of 20. Then, when no air bubbles are confirmed within the observed range, the thickness h is determined as the conformable step d. First tensile test: First, the first alkali glass plate and the second alkali glass plate are bonded in the thickness direction via the optical adhesive sheet to obtain a second bonded body. Next, the optical adhesive sheet is irradiated with an integrated light amount of 3000 mJ / cm. 2 The second bonded body is then heat-treated at 50° C., 0.5 MPa, and 15 minutes. The first and second alkali glass plates in the second bonded body are then pulled in opposite directions in the thickness direction at 85° C. and a pulling speed of 25 mm / min, to measure the adhesive strength B1.

2. The optical adhesive sheet according to claim 1, having an adhesive strength B2 in the second tensile test described below, and a ratio of the adhesive strength B2 to the adhesive strength B1 being 2.0 or more and 3.5 or less. Second tensile test: First, the first alkali glass plate and the second alkali glass plate are bonded in the thickness direction via the optical adhesive sheet to obtain a third bonded body. Next, the optical adhesive sheet is irradiated with an integrated light amount of 3000 mJ / cm. 2 The third bonded body is then heat-treated at 50° C., 0.5 MPa, and 15 minutes. The first and second alkali glass plates in the third bonded body are then pulled in opposite directions in the thickness direction at 25° C. and a pulling speed of 25 mm / min, to measure the adhesive strength B2.

3. The optical adhesive sheet according to claim 1, having an adhesive strength B3 in the third tensile test described below, and a ratio of the adhesive strength B3 to the adhesive strength B1 is 3.0 or more and 4.2 or less. Third tensile test: First, the first alkali glass plate and the second alkali glass plate are bonded in the thickness direction via the optical adhesive sheet to obtain a fourth bonded body. Next, the optical adhesive sheet is irradiated with an integrated light amount of 3000 mJ / cm. 2 The fourth bonded body is then photocured by irradiating it with ultraviolet light at 50° C. for 15 minutes. The fourth bonded body is then heat-treated at 50° C. and 0.5 MPa for 15 minutes. The first and second alkali glass plates in the fourth bonded body are then pulled in opposite directions in the thickness direction at −20° C. and a pulling speed of 25 mm / min to measure the adhesive strength B3.

4. The optical adhesive sheet according to claim 1 , wherein the thickness D is 80 μm or more.

Citation Information

Patent Citations

  • Transparent pressure-sensitive adhesive sheet for flat panel display, and flat panel display

    JP2010097070A